Atividade do óleo essencial de Cymbopogon winterianus Jowitt ex Bor contra Candida albicans, Aspergillus flavus e Aspergillus fumigatus - Oliveira, Wylly Araújo de (2011)
Due increase of incidence of fungal infections for Candida albicans and Aspergillus spp. in immunocompromised patients, and emerging resistant strains to conventional antifungals, it is accentuated the need for new antifungal. Essential oils have been tested for antimycotic activity and possess potential as antifungal agents. This work investigated the activity of essential oil of Cymbopogon winterianus against Candida albicans, Aspergillus flavus and A. fumigatus, by MIC and MFC; time-kill methods and morphological changes in the C. albicans, inhibition of the fungal mycelial growth and analysis of conidia germination of Aspergillus flavus and A. fumigatus when exposed to several concentrations of oil and by cellular leakage and assessed the bind of essential oil with ergosterol. The results shown that essential oil had concentrationdependent antifungal activity, alters the morphology in C. albicans, inhibits conidia germination and the radial mycelia growth of Aspergillus flavus and Aspergillus fumigatus, causes cellular leakage of all strains of fungal species tested and binds to ergosterol. These results make essential oil of Cymbopogon winterianus a potential agent in controlling fungi growth that cause infections, like hospital-acquired infections.